2001
DOI: 10.1038/35068559
|View full text |Cite
|
Sign up to set email alerts
|

Odour-plume dynamics influence the brain's olfactory code

Abstract: The neural computations used to represent olfactory information in the brain have long been investigated. Recent studies in the insect antennal lobe suggest that precise temporal and/or spatial patterns of activity underlie the recognition and discrimination of different odours, and that these patterns may be strengthened by associative learning. It remains unknown, however, whether these activity patterns persist when odour intensity varies rapidly and unpredictably, as often occurs in nature. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
196
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(209 citation statements)
references
References 21 publications
11
196
1
1
Order By: Relevance
“…Using prolonged odor pulses (ranging up to several seconds), studies in locusts and honey bees showed that the timing of PN spiking was phase-locked to multiple cycles of an underlying 20-to 30-Hz oscillation (3,8,17,(21)(22)(23). Other studies in moths, using brief (50-to 200-ms) odor pulses, suggested that synchronous firing between PNs is instead modulated transiently by the variable time course of an intermittent stimulus (4,(9)(10)(11)(12)20). In the present study, we now provide direct evidence from PNs innervating functionally specified glomeruli that the patterns of odorant-evoked synchrony in the AL and LFP oscillations recorded in the same neuropil and in the MB are not temporally correlated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using prolonged odor pulses (ranging up to several seconds), studies in locusts and honey bees showed that the timing of PN spiking was phase-locked to multiple cycles of an underlying 20-to 30-Hz oscillation (3,8,17,(21)(22)(23). Other studies in moths, using brief (50-to 200-ms) odor pulses, suggested that synchronous firing between PNs is instead modulated transiently by the variable time course of an intermittent stimulus (4,(9)(10)(11)(12)20). In the present study, we now provide direct evidence from PNs innervating functionally specified glomeruli that the patterns of odorant-evoked synchrony in the AL and LFP oscillations recorded in the same neuropil and in the MB are not temporally correlated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To address this specific question, we recorded odor-evoked LFP activity from the male-specific MGC and tested with the sex-pheromone blend that specifically activates these glomeruli (4,(9)(10)(11)(12). The pheromone blend was delivered as pulses at different stimulus intensities to simulate a natural wind-borne odor plume (20). As shown in Fig.…”
Section: Different Odor Intensities Yield Different Oscillation Frequmentioning
confidence: 99%
“…To meet the challenge we must modify both our experimental designs and our methods for analyzing the responses to these much more complicated inputs. Recent examples of laboratory based approaches to the problem of natural stimulation are studies of bullfrog auditory neurons responding to synthesized frog calls (Rieke et al , 1995), insect olfactory neurons responding to odour plumes (Vickers et al , 2001), cat LGN cells responding to movies (Dan et al , 1996, Stanley et al , 1999, primate visual cortical cells during free viewing of natural images (Gallant et al , 1998, Vinje andGallant, 2000), auditory neurons in song birds stimulated by song and song-like signals (Theunissen and Doupe, 1998, Theunissen et al , 2000, the responses in cat auditory cortex to signals with naturalistic statistical properties (Rotman et al , 1999), and motion sensitive cells in the fly Egelhaaf, 2001, de Ruyter van Steveninck et al , 2001). In each case compromises are struck between well controlled stimuli with understandable statistical properties and the fully natural case.…”
Section: Introductionmentioning
confidence: 99%
“…In principle this peripheral olfactory structure already seems to be able to discriminate among odors at this early stage. However, the ability to discriminate depends on the number of possible odors, their concentrations, and the complexity in the presence of mixtures [25].…”
Section: Early Codementioning
confidence: 99%
“…The insect brain is our choice to understand the underpinnings of learning because they rely on the olfactory modality and they are simpler than the mammalian counterparts. Moreover, the main brain areas dealing with olfactory processing are fairly well known due to the simplicity of the structural organization [9,10,11,12,13,14,15,16], the nature of the neural coding [17,18,19,20,21,22,23,24,25,26], the advent of the genetic manipulation techniques that isolate brain areas during the formation of memories [27,28,29,30], and the extensive odor conditioning experiments that shed light into the dynamics of learning during discrimination tasks [31,32,33,34,35,6].…”
Section: Introductionmentioning
confidence: 99%